Understanding cyberchondria in pregnant women: longitudinal assessment of risk factors, triggers, and outcomes - Matea Šoštarić; Una Mikac; Nataša Jokić-Begić (Taylor & Francis Group, 2023)
Pregnancy often triggers anxiety and health concerns in women, leading many to search for health information online. Excessive, compulsive, and repetitive online health research, accompanied by heightened anxiety, can result in cyberchondria. This study aimed to explore the risk factors, triggers, and outcomes of cyberchondria in pregnant women. A total of 149 participants completed an online questionnaire longitudinally across three stages of pregnancy: early (14-19 weeks), mid (24-29 weeks), and late pregnancy (34-39 weeks). The findings revealed that health anxiety and the cognitive component of anxiety sensitivity are risk factors for cyberchondria during pregnancy. Pregnancy concerns related to motherhood emerged as triggers for cyberchondria. While a connection between cyberchondria and fear of birth was observed, fear of birth did not appear to be a direct outcome of cyberchondria. These results highlight the importance of addressing health anxiety, cognitive anxiety sensitivity and motherhood concerns in prenatal care and support interventions. Understanding the factors contributing to cyberchondria in pregnant women can assist healthcare professionals in providing targeted support and resources to mitigate excessive online health searching behaviors and alleviate anxiety during pregnancy.